2021
DOI: 10.1038/s41389-021-00315-0
|View full text |Cite
|
Sign up to set email alerts
|

RNF8 ubiquitinates RecQL4 and promotes its dissociation from DNA double strand breaks

Abstract: Ubiquitination-dependent DNA damage response (DDR) signals play a critical role in the cellular choice of DNA damage repair pathways. Human DNA helicase RecQL4 participates in DNA replication and repair, and loss of RecQL4 is associated with autosomal recessive genetic disorders characterized by genomic instability features. In an earlier study, RecQL4 was isolated as a stable complex that contained two ubiquitin ligases of the N-end rule (UBR1 and UBR2). However, it is unknown whether or not RecQL4 ubiquitina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…Cellular extracts from RECQL4 knockdown cells have decreased capacity to join DNA ends in vitro . This was recapitulated in vivo as RECQL4 knockdown leads to decreased NHEJ using a GFP reporter system and similar results were later confirmed by others [ 52 , 74 , 89 ]. Shamanna et al also demonstrated that RECQL4 physically and functionally interacts with the key NHEJ protein, KU70, in the N-terminus of RECQL4.…”
Section: Role Of Recql4 During Dna Double-strand Break Repairsupporting
confidence: 77%
See 2 more Smart Citations
“…Cellular extracts from RECQL4 knockdown cells have decreased capacity to join DNA ends in vitro . This was recapitulated in vivo as RECQL4 knockdown leads to decreased NHEJ using a GFP reporter system and similar results were later confirmed by others [ 52 , 74 , 89 ]. Shamanna et al also demonstrated that RECQL4 physically and functionally interacts with the key NHEJ protein, KU70, in the N-terminus of RECQL4.…”
Section: Role Of Recql4 During Dna Double-strand Break Repairsupporting
confidence: 77%
“…Furthermore, addition of RECQL4 increases KU complex DNA binding in vitro [ 52 ]. KU complex interaction with RECQL4 was later confirmed in vivo ( Table 2 ) [ 74 , 89 ]. Lu et al demonstrated that RECQL4 interacts with KU70 in a cell cycle dependent manner with increased interaction during the G1 stage, when NHEJ is the predominant DSB repair pathway ( Figure 3 C) [ 74 , 90 ].…”
Section: Role Of Recql4 During Dna Double-strand Break Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the residues required for RECQ4 recruitment to DNA damage sites have been identified ( Singh et al, 2010 ), it is yet to be determined if these residues are involved in direct DNA damage recognition or RECQ4 re-localization to the damage site via protein-protein interaction(s). Once bound to the DNA damage, RECQ4 requires RNF8-dependent ubiquitination at its C-terminus to dissociate from the site of DNA damage, allowing downstream DNA repair factors to bind to the damage site ( Tan et al, 2021 ). While studies show that RECQ4 positively regulates homologous recombination and non-homologous end joining, RECQ4 suppresses the repair of DNA breaks via RAD52-mediated single-strand annealing pathway via its SF2 and/or the C-terminal domains ( Kohzaki et al, 2020 ).…”
Section: Recq4 In Dna Repairmentioning
confidence: 99%
“…These enhanced activities were not observed in cells expressing the del(Ala420-Ala463) mutant protein, providing an explanation for why cells expressing Pro466Leu RECQ4 mutant do not contain high levels of mtDNA compared to those expressing the del(Ala420-Ala463) mutant ( Croteau et al, 2012b ; Wang et al, 2014 ; Chang et al, 2020 ). It would be a great interest to determine if the enhanced nucleic acid affinity by the Pro466Leu mutation may retain RECQ4 at DNA damage sites, hindering the binding and access of downstream DNA repair factors ( Tan et al, 2021 ). Nonetheless, another report showed that Pro466Leu, Phe637Ser and Phe697Leu disease mutations decrease RECQ4 DNA binding ( Jensen et al, 2012 ).…”
Section: Recq4 Biochemical Propertiesmentioning
confidence: 99%